Telaah Hukum Sewa Rumah Kontrakan dalam Perspektif Islam: Studi Konseptual Akad Ijarah dan Implikasinya - Ananda Ma; Sargini; Jauharudin (CV. Kalimasada Group, 2025)
The practice of renting out rented houses often raises legal issues, such as the unclear contract and the responsibilities of the parties involved, so it is important to study it from an Islamic legal perspective through the concept of the ijarah contract. This study aims to examine the practice of house rental contracts from the perspective of Islamic law, focusing on the concept of the ijarah contract and the principles of muamalah. The methodology employed is a literature review, which involves collecting information from classical Islamic jurisprudence, fatwas, academic journals, and relevant legal regulations. The findings indicate that the ijarah contract is recognized as a valid transaction in Islam, provided it fulfills the necessary pillars and conditions, such as clarity of the object, mutual consent (ijab and qabul), and agreement on compensation. However, in practical applications, several issues often arise, such as unwritten contracts, unclear responsibilities, and unjust pricing. Therefore, the implementation of sharia principles-such as justice, transparency, and mutual consent is crucial. This study recommends the formulation of written agreements and the integration of sharia principles into national legal frameworks to promote fair and sustainable rental transactions.